PROJECTED FLOW ALTERATION AND ECOLOGICAL RISK FOR PAN‐EUROPEAN RIVERS. (25th February 2013) - Laizé, C. L. R.; Acreman, M. C.; Schneider, C.; Dunbar, M. J.; Houghton‐Carr, H. A.; Flörke, M.; Hannah, D. M.
ABSTRACT Projection of future changes in river flow regimes and their impact on river ecosystem health is a major research challenge. This paper assesses the implications of projected future shifts in river flows on in‐stream and riparian ecosystems at the pan‐European scale by developing a new methodology to quantify ecological risk due to flow alteration (ERFA). The river network was modelled as 33 668 cells (5′ longitude × 5′ latitude). For each cell, modelled monthly flows were generated for an ensemble of 10 scenarios for the 2050s and for the study baseline (naturalized flows for 1961–1990). These future scenarios consist of combinations of two climate scenarios and four socio‐economic water‐use scenarios (with a main driver of economy, policy, security or sustainability). Environmental flow implications are assessed using the new ERFA methodology, based on a set of monthly flow regime indicators (MFRIs). Differences in MFRIs between scenarios and baseline are calculated to derive ERFA classes (no, low, medium and high risk), which are based on the number of indicators significantly different from the baseline. ERFA classes are presented as colour‐coded pan‐European maps. Results are consistent between scenarios and show that European river ecosystems are under significant threat with about two‐thirds at medium or high risk of change. Four main zones were identified (from highest to lowest risk severity): (i) Mediterranean rim, southwest part of Eastern Europe and Western Asia; (ii) Northern Europe and northeast part of Eastern Europe; (iii) Western and Eastern Europe; and (iv) inland North Africa. Patterns of flow alteration risk are driven by climate‐induced change, with socio‐economics as a secondary factor. These flow alterations could be manifested as changes to species and communities, and loss of current ecosystem functions and services. Copyright © 2013 John Wiley & Sons, Ltd.